Between Expectations and Demands: The Dynamics of Quarter-Life Crisis in the Sandwich Generation - Kurnianingtyas, Kurnianingtyas; Kawuryan, Fajar (Psikostudia : Jurnal Psikologi, 2026)
Young adulthood is a developmental phase marked by identity exploration, career uncertainty, and future planning, which often gives rise to a quarter-life crisis. These challenges become more complex when individuals simultaneously carry dual responsibilities as part of the sandwich generation, supporting both parents and their own nuclear families. This study aims to explore the dynamics of quarter-life crisis among young adults in the sandwich generation. Using a qualitative phenomenological approach, three participants aged 22–25 were selected through purposive and snowball sampling. Data were collected through semi-structured interviews, non-participant observation, and documentation, and analyzed thematically. The findings indicate that the quarter-life crisis experienced by sandwich-generation individuals is shaped by three interrelated factors: individual factors (identity confusion, emotional exhaustion, and feelings of failure), social factors (family expectations, cultural pressures, and role-related conflicts), and economic factors (income instability, dual financial responsibilities, and unexpected expenses). The interaction of these factors creates an existential crisis characterized by feelings of being trapped, loss of direction, and postponement of personal aspirations in favor of family obligations. The study highlights the psychological vulnerability of young adults in the sandwich generation and underscores the importance of social support, emotional regulation skills, and targeted psychological interventions to help them manage role-related pressures more adaptively.